Становлення та розвиток філософсько-правових ідей в Галичині (сер. XIX – XX ст. ст.) - Вовкович, Уляна Володимирівна (Національний університет "Львівська політехніка", 2018)
Дисертація є першим комплексним дослідженням процесів становлен-ня і розвитку філософсько-правових ідей в Галичині сер. XIX – XX ст.ст. У роботі проаналізовані передумови появи філософсько-правової теорії на розмежованих і поневолених західноукраїнських землях. Здійснений теоретичний аналіз суспільно-політичних умов зародження філософсько-правової теорії, появи діалектичних підходів до проблем людини і права в умовах бездержавності, підвищення правосвідомості населення Галичини. Розглянуті недосліджені і мало вивчені праці правників Галичини сер. ХІХ–ХХ ст.ст. К. Ганкевича, К. Левицького, С. Дністрянського, В. Старосольського та ін. Вивчено появу в Галичині філософсько-правових ідей у вітчизняній гуманітаристиці та їхнє становлення в сер. ХІХ–ХХ ст.ст., осмислення процесів розвитку національної філософії не локально, а в органічній єдності та спорідненості із європейським правовим контекстом; акцентовано аксіологічні архетипи слов’янського філософського дискурсу ХVІ–ХVІІІ ст.ст., продовжені правниками-науковцями Галичини в аналізований період; зауважено на наявності західноукраїнського філософського романтизму у вимірі європейського разом із його кризою в ХІХ ст. та наявності чотирьох етапів розвитку філософсько-правових ідей в Галичині в сер. ХІХ–ХХ ст.ст. Диссертация является первым комплексным исследованием процессов становления и развития философско-правовых идей в Галичине сред. XIX – XX вв. В работе проанализированы предпосылки возникновения философско-правовой теории на разделенных и угнетенных западноукраинских землях. Совершен теоретический анализ общественно-политических условий возникновения философско-правовой теории, появления диалектических подходов к проблемам человека и права в условиях отсутствия государственности, повышения правосознания населения Галичины. Рассмотрены неисследованные и мало изученные труды юристов Галичины сред. XIX–XX вв. К. Ганкевича, К. Левицкого, С. Днистрянского, В. Старосольского и др. Исследовано появление в Галичине философско-правовых идей в отечественной гуманитаристике, а также становление их в сред. XIX–XX веков, осмысление процессов развития национальной философии не в локальном измерении, а в органическом единстве и родстве с европейским правовым контекстом; акцентированы аксиологические архетипы славянского философского дискурса XVI–XVIII в.в., развиты юристами-учеными Галичины в анализированный период; сосредоточено внимание на присутствии западноукраинского философского романтизма в измерении европейского вместе с его кризисом в XIX в. и наличии четырех этапов развития философско-правовых идей в Галичине в сред. XIX–XX в.в. The dissertation is the first comprehensive research of the statement and development of philosophical and legal ideas in Galicia in the middle of the XIX–XX centuries. In the thesis the preconditions of the appearance of the philosophical and legal theory are analyzed on the divided and enslaved West Ukrainian lands. Theoretical analysis of social and political conditions for the emergence of philosophical and legal theory, the emergence of their dialectical approaches to human problems and rights in conditions of non-statehood increasing, the legal awareness of the population are considered. Unknown researches of Galician lawyers of the middle of the XIX–XX centuries such as K. Hankevich, K. Le-vitsky, S. Dnistryansky, V. Starosolsky and others are under research. The appearance in Galicia of philosophical and legal ideas in the national humanities and their formation in the heart have been considered in the middle of the XIX–XX centuries, comprehension of processes of development of national philosophy is not locally, but in organic unity and affinity with the European legal context; the axiological archetypes of the Slavic philosophical discourse of the XVІ-ХVIII centuries, which were continued by lawyers-scientists of Galicia in the mentioned period, were emphasized; It was noted that Western Ukrainian philosophical romanticism in the dimension of European one, with its crisis in the nineteenth century were together; and the availability of four stages of the development of philosophical and legal ideas in Galicia in the middle of XIX–XX centuries is considered. The first and most reasoned conclusion about the general processes of the development of the philosophy of law in Galicia is the presence of all its features of Europe in it. By adopting principles of Europe and through its involvement in other factors of the spiritual Europe, with its pre-Christian origins in the direction of European culture, Ukrainian culture organically manifested its features. The awareness of such an accessory has been proven by the highly educated lawyers, who grew and became established thanks to the philosophy of law with con-tinuous national-cultural traditions – from the end of the XVIth to the beginning of the XVIIIth century, the middle of the XIX century, and further – in the first decades of the XX century. Active research activities of Galician lawyers can be the confirmation of their national values and identity. In a tragic history Galician researchers did not lose their own face, preserved – albeit in a «capsule» versions – the roots of culturally progressive philosophy. It was about law and justice, equality and justice, which naturally fit into the ideological dominant to overcome problems of this time. From the initiated Western-Ukrainian philosophical and legal discourse of the Galicia lawyers, in the middle of the XIX–XX centuries resulted not solved yet problems of contemporary philosophical jurisprudence: 1) the need for continued deep research of the legal heritage of Galicia, which is not for archive but for historical objectivity and naturalness of Ukrainian discourse with features of the European style of philosophy; 2) continuation of the philosophical and legal-linguistic investigations initiated by K. Levitskiy, for produce of its own professional legal language, which will contribute to solving urgent issues of modern philosophical and legal science; 3) researching the processes of development of Ukrainian philosophy of law as a unified system of measurement of this science in territory of Ukraine and its large separated territories and the comparison of the same stage of legal philosophy in Russian empire.
Становление и развитие философско-правовых идей в Галичине (сред. XIX – XX вв.)
Statement and development of philosophical and legal ideas in Galicia (middle of the XIX – XX centuries)
Keywords: філософсько-правові ідеї; еволюційні епістемологічні ідеї; онтосфера ідей; аксіологічний денотат; цивілізаційні процеси; умови роз’єднаності українських земель; поневолення Галичини; умови бездержавності; ідеологія спотворень; єдність із європейським контекстом; философско-правовые идеи; эволюционные эпистемологические идеи; онтосфера идей; аксиологический денотат; цивилизационные процессы; условия разъединенности украинских земель; угнетение Галичины; условия отсутствия государственности; идеология искажения; единство с европейским контекстом; philosophical and legal ideas; evolutionary epistemological ideas; ontosphere of ideas; axiological denotate; civilization processes; conditions of division of Ukrainian lands; enslavement of Galicia; conditions of non-statehood; ideology of distortions; unity with the European context; 340.12